Long Live Patriarchy: Love in the Time of ‘Abd al-Wahhab - Armbrust, Walter (History compass, 2009)
This paper is part of a History Compass conference cluster tracing the formation of national culture in Egypt. Guest edited by Walter Armbrust, this cluster of articles was originally part of a conference in Oxford on January 12-13, 2007, organized by Walter Armbrust, Ronald Nettler, and Lucie Ryzova, and funded by the Middle East Centre (St. Antony's), The Faculty of Oriental Studies, The Khalid bin ‘Abdullah Al-Sa’ud Professorship (Professor Clive Holes), and The Centre for Political Ideologies.